Changes in Seizure Frequency and Antiepileptic Therapy During Pregnancy. Issue 3 (25th September 2021) - Pennell, P.B.; French, J.A.; May, R.C.; Gerard, E.; Kalayjian, L.; Penovich, P.; Gedzelman, E.; Cavitt, J.; Hwang, S.; Pack, A.M.; Sam, M.; Miller, J.W.; et al.
Abstract : ( N Engl J Med . 2020;383:2547–2556) The management of pregnant women with epilepsy involves weighing the need to control seizures with the risks of antiepileptic drugs negatively affecting the development of the fetus. Epilepsy is associated with higher rates of maternal mortality compared with nonepileptic mothers. Pregnancy has been reported to increase the rate of seizures in women with epilepsy. This study aimed to compare the frequency of seizures in pregnant and nonpregnant women and investigated changes in required doses of antiepileptic drugs in pregnant women compared with nonpregnant women.